Pathways to Financial Stability: Insights from Indonesia - Tetty Lasniroha Sarumpaet; Bunga Indah Bayunitri; Irene Sukma Lestari; Dinayanti Zanetta; Sarah Lutfiah Zahra (Lembaga Riset dan Inovasi Al-Matani, 2026)
This study examines the effects of financial literacy, financial behavior, and financial stress on financial well-being among low-income individuals in Indonesia. It also investigates the mediating role of financial behavior in the relationships between financial literacy, financial stress, and financial well-being. Using a quantitative approach, data were collected through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that financial literacy positively influences both financial well-being and financial behavior, highlighting the important role of financial knowledge in improving individuals’ financial conditions. In contrast, financial behavior does not significantly influence financial well-being, suggesting that responsible financial practices alone may not be sufficient to improve financial outcomes among low-income groups facing structural economic constraints. The study also reveals that financial stress has a positive relationship with financial well-being and financial behavior, although these findings differ from the hypothesized direction and therefore require careful interpretation. Furthermore, financial behavior does not mediate the relationships between financial literacy, financial stress, and financial well-being. These findings emphasize the dominant direct role of financial literacy in enhancing financial well-being among economically vulnerable populations. This study contributes to the financial well-being literature by demonstrating that financial behavior does not always function as an effective transmission mechanism in low-income contexts. Practically, the study suggests that financial education programs should focus on strengthening financial knowledge, financial confidence, and decision-making capacity while also addressing structural financial challenges faced by low-income individuals.